2021
DOI: 10.1038/s41598-021-02032-5
|View full text |Cite
|
Sign up to set email alerts
|

A demographic and clinical panorama of a sixteen-year cohort of soft tissue sarcoma patients in Brazil

Abstract: Little is known about soft tissue sarcomas (STS) in Brazil, once the federal statistics regarding estimates on incidence and mortality of the most common cancers that affect the Brazilian population currently do not include STS. This study aims to perform a broad evaluation and description of the epidemiological profile, access to treatment and main clinical outcomes of the Brazilian STS patient. A population-based cohort study of 66,825 patients who underwent procedures related to STS treatment registered in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…The data reported in several studies do not show a gender distribution; however, our results show an almost uniform distribution between genders, with a slight majority of patients being male (50.61%) and living in the highlands, results that are similar to those published by Bozzo et al in Canada [ 11 ] in a five-year cohort study. However, these data are in contrast with those reported in Brazil in a sixteen-year cohort study where soft-tissue sarcomas were reported to be slightly higher in females [ 12 ]. The results of this study in this sense resemble those of a ten-year retrospective cohort study in Germany that reported an even distribution between genders [ 13 ].…”
Section: Discussioncontrasting
confidence: 92%
“…The data reported in several studies do not show a gender distribution; however, our results show an almost uniform distribution between genders, with a slight majority of patients being male (50.61%) and living in the highlands, results that are similar to those published by Bozzo et al in Canada [ 11 ] in a five-year cohort study. However, these data are in contrast with those reported in Brazil in a sixteen-year cohort study where soft-tissue sarcomas were reported to be slightly higher in females [ 12 ]. The results of this study in this sense resemble those of a ten-year retrospective cohort study in Germany that reported an even distribution between genders [ 13 ].…”
Section: Discussioncontrasting
confidence: 92%
“…7 However, limb amputation severely limits functional ability. Extremity STS affects people with a median age in the 50s, 8 who are usually socioeconomically active in society, as in our patients. Chemotherapy for STS has increased the 5-year survival rates with localized tumors up to 60%.…”
Section: Discussionmentioning
confidence: 73%
“…The elegant analysis by Figueiredo and colleagues highlights the paucity and poor quality of available data in Brazil. 21 In this report, sarcomas with an unspecified location or identified as invasive but lacking a precise location constituted 29.7% of the study group. Moreover, tumour grade and clinical staging sub-registrations were noted, with grade X (undefined) and indeterminate clinical stage being the most frequently recorded for these variables, at 91.3% and 79.5% respectively.…”
Section: Cancer and Sarcoma Epidemiology In Latin Americamentioning
confidence: 64%
“…Examples include research by Dr DelaGarza-Montano examining the epidemiology of musculoskeletal tumours at Mexico City's National Rehabilitation Institute, by Dr Lopes David evaluating sarcoma burden and pathways in hospital-based registries in Brazil, by Dr Chávez describing patients with soft tissue sarcoma treated at the National Institute of Neoplastic Diseases of Peru, and by Dr Figueiredo evaluating public databases in Brazil, among others. 8 , 19 , 20 , 21 The single publication addressing the incidence of soft tissue sarcomas in the region based on a Population-based Cancer Registry is from the City of São Paulo, Brazil, in which it was estimated to be 3.36/100.000 habitants. 21 …”
Section: Cancer and Sarcoma Epidemiology In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation